Right of access to health care of older persons in Mexico: critical discursive reflection - Guerrero-Castañeda, Raúl Fernando (Universidad de Sonora, 2019)
Introduction: Changes in health conditions have increased people’s life expectancy. The right to health care is fundamental and universal, so older persons should enjoy this right without limitations. Objective: Reflect on conditions for access to health care for the elderly from the perspective of universal rights. Development: This is a reflective study based on the review of literature as well as critical viewpoints from the authors. Health care as a right is within the framework of international declarations and agreements between countries, as a sustainable commitment to the attention of an aging population. Mexico has strategies such as the General Health Law, Law on the Rights of Older Persons, and the Plan of Attention to Aging Population. Conclusions: Even though health is a universal right, efforts are still required in order for an elderly Mexican person to enjoy this right abundantly and to satisfaction, thus dignifying those in old age.